Letter to the editor: female sex workers and HPV vaccine. Issue 1 (2nd January 2020) - Brown, Brandon; Cabral, Alejandra
ABSTRACT: Schim van der Loeff et al. weigh the pros and cons of offering HPV vaccines to female sex workers (FSWs). This is a pressing question in areas where the vaccine is not routinely available to all and vaccine resources are limited. In many countries, current FSWs would have missed the opportunity for vaccination as part of nationwide campaigns to reach school-age girls. Offering the HPV vaccine at the time of sex worker registration may protect them from acquiring high risk HPV types from future clients. A critical mistake in academic writing is excluding the population of interest from contributing to discussions about their health. Without the perspective of FSWs as authors, we are not engaging in good participatory practices.